The Effect of Payment Methods on Dental Service Mix: An Economic Retrospective Cohort Study - Reza Emrani; Katayoun Sargeran; Hossein Hessari (Wolters Kluwer Medknow Publications, 2021)
Introduction: The number of dental services provided is related to the type of services needed by a population and treatment decision making by dentists. This descriptive study aimed to compare the dental service mix in two different payment systems. Methods: The dental records of a long-established dental clinic were reviewed. Treatment performed, during October 2018 and October 2019, by 36 dentists, 12 dentists worked in both payment method periods, 12 of them worked only in salary, and 12 of them worked in fee for service (FFS) period. Results: Preventive dental services and practices without treatment (visits, diagnostic radiography, and referrals) decreased, and practices included aggressive treatments (randomized controlled trial, extraction, and crown) and highly aggressive procedure (surgery) increased from salary to FFS period. The total activities of dentists were higher in FFS. Conclusion: According to our results, in a salary system, the dentist was more likely to refer and perform preventive treatments, whereas in the FFS payment system, the dentists choose more aggressive treatments. Payment method may change dental service mix.